Creative Commons Licences, the Copyright Regime and the Online Community: Is there a Fatal Disconnect? - Corbett, Susan (Modern Law Review, 2011)
Creative works on the Internet (online works) present challenges to the traditional copyright model. Creative Commons licences are one response to these challenges. Despite the many positive features of Creative Commons licences, certain aspects have attracted criticism. The flaws in Creative Commons licences are a symptom of a broader failure of the copyright system itself to engage with the community. Creative Commons licences operate within the traditional copyright model, despite having some resonance with a developing copyright paradigm. Yet many concepts of copyright are not understood by the wider community; indeed, some remain a source of ongoing debate within the legal academy. Furthermore, there is evidence that community norms and expectations in relation to online works conflict with the legal environment provided by copyright law. The author argues that until these issues are addressed, an attempt to reconceptualise the legal environment by working within its constraints is unlikely to be successful.